On Biometrics Feature Extraction and Template Security Schemes - Khurshid, Mahapara; Selwal, Arvind (International Journal of Computer Sciences and Engineering, 2025)
Effective response to identification and authentication of individuals in complex environment demands replacement of traditional authentication techniques. It should occur concurrently with the increased pace of the digital world and increasing population. Many unimodal template security systems have been published, but in one or the other way, they are associated with some technical flaws, which prevents them from claiming to be reliable models. After doing the critical review of many published articles and case studies, many design characteristics of template security systems like security level, reliability, privacy level, acceptability, performance, uniqueness and cost, were taken into consideration for analyzing the various available models. However, no model was found to be associated with all the design parameters, which could claim to be a highly secure and reliable model. On review basis, it was found that many design characteristics were underestimated, if taken into consideration for development and implementation, could revolutionize biometric based template security systems.